Correction: Baucum II, Anthony J. et al. Proteomic Analysis of the Spinophilin Interactome in Rodent Striatum Following Psychostimulant Sensitization. Proteomes 2018, 6, 53 - Darryl S. Watkins; Jason D. True; Amber L. Mosley; Anthony J. Baucum (Proteomes, 2019)
The author wishes to make the following corrections to the methods section of their paper [...]